«Chi potrebbe esplicar con parole»: il lessico dei disastri nelle relazioni di età moderna tra scarti e continuità - Rosa Anna Paradiso (Laboratoire Italien)
In this contribution we try to bring together two lines of investigation that have recently concerned historical-linguistic research on disaster reports in Italy, that is, the study of the lexicon of natural disasters and the study of the language of the news press. With an analysis conducted on a corpus of seventy-five relazioni on disasters that occurred in southern Italy, published between 1538 and 1707, we particularly examine some linguistically and stylistically innovative features of reports on disasters in the early modern period. Ultimately, these elements are linked to the impossibility of describing, with traditional words and styles, an event that requires, at this chronological stage, the use of new terms and analogies: hence the use of dialect and the use of modern descriptive topoi such as those of war and spectacle. At the same time, we observe how a new discursive tradition is being created in the early modern period, exemplified on the one hand by the continuity in the use of syntagms that cannot be seen in the repertoires and the aforementioned descriptive strategies, and on the other by the affirmation of a sensationalist approach to information about the disaster. This direction –which has points in common with contemporary news– seems in turn to go hand in hand with the progressive definition, at least in the printer’s intentions, of the editorial product.